Exact form : 4/3
decimal form : 1.3
Answer:
Step-by-step explanation:
y=(2x²+x)³+(x-1)/(1-x)
=(2x²+x)³+(x-1)/-(x-1)
=(2x²+x)³-1
dy/dx=3(2x²+x)(4x+1)-0
=3x(2x+1)(4x+1)
Answer:
(18, ∞)
Step-by-step explanation:
(18, ∞) is the only option that works. if we ignore the "greater than" sign, and just set the function equal to -12, we see that x-10=-12 would give us x=-2. If we plug in -3 for x, we get -13, which is less than -12. if we plug in -1 for x, we get -11, which is greater than -12. Therefore, with the function only having one critical point (zero), we know that every value greater than -2 is a solution. Technically, the full solution would be (-2, ∞). however, the only answer available meeting the criteria would be (18, ∞).
12 2 +16 2 = D2
D2= 144+256
D2= 400
D2= 400